Effectiveness of the Implementation of Occupational and Safety Health Management System (OSHMS) on Pine Resin Harvesting - Septiana, Ratih Madya; Iwaoka, Masahiro; Matsumoto, Takeshi (Institut Pertanian Bogor (IPB University), 2024)
Work in the forestry sector, especially pine resin harvesting, is classified as heavy work and a high risk of accidents and occupational health because the pine resin harvesting activities are carried out on varying topography, using various heavy tools and hazardous chemicals. Hence, the occupational and safety health management system (OSHMS) is an essential sector. Some studies about pine resin tapping focused on productivity, socio-economics, and resin quality; however, there needs to be more research about OSHMS in pine resin harvesting. Therefore, the effectiveness of implementing OSHMS is essential to analyze, finding out its impact on the rate of work accidents and employee health in forest product harvesting activities. The objectives of this study are a) to identify the sociodemographics of forest employees, b) to clarify the pine resin harvesting activities and identify the hazard risk, and c) to clarify the effectiveness of the implementation of OSHMS on pine resin harvesting activities. The research was conducted in the state forest company (SFC) in Central Java Province. Interview techniques, literature studies from OSH documents, and field observations carried out to collect sociodemographics of forest employees are dominated by old employees, low education levels, and a working system based on family; this situation impacts the implementation of OSHMS and pine resin harvesting. The SFC provides SOP and training about the technical application of pine resin harvesting, but some employees did not follow the procedure. The impact of disobeying employees, the hazard risk, and accidents also improve. The recommendations for the company are to increase the time spent training the workers and to implement the OSHMS standard. Personal protective equipments have to check routines, and the employees must know the mechanism if there is an accident and how to solve it.